The Influence of Facilities and Service Quality on Customer Satisfaction at Oma Kulina Restaurant Bintaro - Maeliya Fadhilah; Vivi Ristanti (Asosiasi Dosen Muda Indonesia, 2026)
Customer satisfaction has become a strategic priority in the restaurant industry because it influences customer loyalty, revisit intention, and long-term business sustainability. Although previous studies consistently identify service quality as a major determinant of customer satisfaction, empirical evidence regarding the contribution of physical facilities remains inconsistent across different service contexts. This study aims to examine the influence of facilities and service quality on customer satisfaction at Oma Kulina Restaurant Bintaro while evaluating the relative importance of both variables within an Indonesian restaurant setting. A quantitative research design was employed using purposive sampling. Primary data were collected through structured questionnaires distributed to 84 customers who had visited the restaurant at least twice. Data were analyzed using multiple linear regression with SPSS. The findings reveal that service quality has a positive and significant effect on customer satisfaction (β = 1.358; p < 0.001), whereas facilities do not significantly influence customer satisfaction (β = 0.048; p = 0.463). Simultaneously, facilities and service quality significantly explain customer satisfaction, accounting for 80.8% of the variance (R² = 0.808). These findings indicate that customers prioritize interpersonal service quality over physical facilities when evaluating their restaurant experiences. This study contributes to the service marketing literature by extending the application of Expectation Confirmation Theory and the SERVQUAL framework within the Indonesian restaurant industry. The findings also provide practical recommendations for restaurant managers to prioritize employee service quality while maintaining adequate physical facilities to strengthen customer satisfaction and competitive advantage.